NAVIGATING ENGLISH AS A LINGUA FRANCA IN A CROSS-CULTURAL CLASSROOM: A PHENOMENOLOGICAL STUDY OF AN INDONESIAN SEA-TEACHER’S PEDAGOGICAL ADAPTATION - Agustina Gultom; Sri Wachyunni; Hustarna Hustarna; Mukhlash Abrar; Hadiyanto Hadiyanto (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Teaching in another country can broaden pre-service teachers’ understanding of classroom practice; however, encounters with diverse varieties of English and different interactional conventions often require communicative and pedagogical adjustments that are not fully addressed in initial preparation. This article examines the experience of an Indonesian pre-service English teacher during a one-month SEA-Teacher placement at a public junior high school in Iloilo Province, Philippines. It explores how the participant navigated communicative and pedagogical uncertainty, interpreted student responses, modified instructional decisions, and reconsidered her understanding of the teacher’s role. An interpretive single-case study informed by hermeneutic phenomenology was used to examine this experience. The data comprised three serial interviews, twenty daily reflective journal entries, eight revised lesson plans, twelve photographs of classroom whiteboards, and four mentor notes. Using Reflexive Thematic Analysis, the data were read repeatedly, coded inductively, compared across sources, and developed into interconnected themes. Unfamiliar pronunciation, classroom expressions, and student silence prompted the participant to simplify instructions, allow multilingual responses, and use examples grounded in local life. The study proposes the Adaptive Navigation Cycle as a single-case conceptual synthesis linking dissonance, contextual meaning-making, pedagogical improvisation, and professional reflection. The findings point to the need for preparation in English as a Lingua Franca, structured reflective journaling, and cross-border mentor support throughout international teaching mobility. ABSTRAK Pengalaman mengajar di negara lain dapat memperluas cara calon guru memahami kelas, tetapi perjumpaan dengan ragam bahasa Inggris dan kebiasaan interaksi yang berbeda sering menuntut penyesuaian komunikatif dan pedagogis yang tidak sepenuhnya tercakup dalam persiapan awal. Artikel ini mengkaji pengalaman seorang calon guru bahasa Inggris asal Indonesia selama penempatan SEA-Teacher satu bulan di sebuah sekolah menengah pertama negeri di Provinsi Iloilo, Filipina. Kajian menelusuri cara partisipan menghadapi ketidakpastian komunikatif dan pedagogis, menafsirkan respons siswa, mengubah keputusan pembelajaran, serta menata ulang pemahamannya tentang peran guru. Studi kasus tunggal interpretatif dengan pendekatan fenomenologi hermeneutik digunakan untuk membaca pengalaman tersebut. Data mencakup tiga wawancara serial, dua puluh jurnal reflektif harian, delapan rencana pembelajaran revisi, dua belas dokumentasi papan tulis, dan empat catatan mentor. Melalui Reflexive Thematic Analysis, data dibaca berulang, dikodekan secara induktif, dibandingkan lintas sumber, lalu dirangkai menjadi tema-tema yang saling berhubungan. Ketidakakraban terhadap pelafalan, ekspresi kelas, dan keheningan siswa mendorong partisipan menyederhanakan instruksi, membuka respons multibahasa, serta menggunakan contoh yang dekat dengan kehidupan lokal. Studi ini mengajukan Adaptive Navigation Cycle sebagai sintesis konseptual berbasis satu kasus yang menghubungkan disonansi, pemaknaan konteks, improvisasi pedagogis, dan refleksi profesional. Temuan ini mengarah pada perlunya pembekalan English as a Lingua Franca, jurnal reflektif terstruktur, dan pendampingan mentor lintas negara selama mobilitas mengajar.